Market Reform: Is It for Real? - DING, David K. (Institutional Knowledge at Singapore Management University, 1999)
This volume contains business reports originating from the Business Study Mission to northeastern China in December 1997. Over a 15 day period, 48 participants explored the climate for business opportunities in Beijing, Hebei and Liaoning provinces.